2017
DOI: 10.3390/plants6020015
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Raft, Regulator of Plasmodesmal Callose Homeostasis

Abstract: The specialized plasma membrane microdomains known as lipid rafts are enriched by sterols and sphingolipids. Lipid rafts facilitate cellular signal transduction by controlling the assembly of signaling molecules and membrane protein trafficking. Another specialized compartment of plant cells, the plasmodesmata (PD), which regulates the symplasmic intercellular movement of certain molecules between adjacent cells, also contains a phospholipid bilayer membrane. The dynamic permeability of plasmodesmata (PDs) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 85 publications
1
32
0
Order By: Relevance
“…The lipid composition of PDs is enriched in sterols and sphingolipids with very long chain saturated fatty acids (Grison et al 2015). This is reminiscent of DRMs and, consistent with this finding, members of the Remorin family and GAPs that are enriched in DRMs locate to PD (Raffaele et al 2009;Fernandez-Calvino et al 2011;Iswanto and Kim 2017).…”
Section: Association Of Gaps With Plasmodesmata In a Lipid-dependent supporting
confidence: 73%
“…The lipid composition of PDs is enriched in sterols and sphingolipids with very long chain saturated fatty acids (Grison et al 2015). This is reminiscent of DRMs and, consistent with this finding, members of the Remorin family and GAPs that are enriched in DRMs locate to PD (Raffaele et al 2009;Fernandez-Calvino et al 2011;Iswanto and Kim 2017).…”
Section: Association Of Gaps With Plasmodesmata In a Lipid-dependent supporting
confidence: 73%
“…Lipid raft is a unique platform comprised by phospholipids, sterol and SLs that highly enriched in the PD-PM. Moreover, it was shown that PdBG2 protein, which attributes with lipid rafts at PD is mislocalized and induced callose deposition upon sterol depletion (Mongrand et al, 2004; Borner et al, 2005; Grison et al, 2015; Iswanto and Kim, 2017), and this subcellular localization alteration was also observed in the N. benthamiana leaves transiently expressing GFP:PdBG2 after Fen treatment ( Supplemental Fig. S3 ).…”
Section: Discussionmentioning
confidence: 88%
“…These intercellular channels play important roles in multicellular events during plant development by allowing the molecular exchange of signaling molecules such as transcription factors, RNAs, and growth regulators (Zambryski and Crawford, 2000; Maule, 2008; Wu et al, 2018). The plasmodesmal plasma membrane (PD-PM) is distinct from general cellular plasma membrane (PM) and is characterized by the enrichment of sterols and sphingolipid SL species (Grison et al, 2015; Iswanto and Kim, 2017; Mamode Cassim et al, 2019). The domains enriched with those special lipids are referred to as the membrane microdomain compartments, also called lipid rafts (Mongrand et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a possible cause for the differences in the behaviour and localization of PDLP1 and PDLP5 has been identified [82]. Pd-lining plasma membrane is known to contain specific regions in which sphingolipids interact with sterols to create specialized domains [106,108,109], where GPI-anchored proteins accumulate [39,56]. Moreover, sphingolipid biosynthesis is very important for modulating Pd function [110].…”
Section: Plasmodesmata-located Protein 5 (Pdlp5)mentioning
confidence: 99%